Bioactivity and DNA/BSA Interactions of Selenium N‐Heterocyclic Carbene Adducts. Issue 35 (16th September 2020) - Ashraf, Rizwan; Iqbal, Muhammad Adnan; Bhatti, Haq Nawaz; Janjua, Muhammad Ramzan Saeed Ashraf; El‐Naggar, Mohamed
Abstract: In wake of promising biomedical applications of organo‐selenium compounds, the present work was planned to synthesize selenium adducts (1 s ‐‐4 s ) and their respective azolium ligands (1 a –4 a ), which were subsequently authenticated by various analytical and spectroscopic techniques like microanalysis, UV‐Visible, FT‐IR, 1 H & 13 C NMR and Electrospray Ionisation‐Mass Spectrometry (ESI‐MS). Moreover, the synthesized compounds were tested for their biological potential like antioxidant, antimicrobial, hemolytic, DNA and Bovin Serum Albumin (BSA) interactions, stability and lipophilicity using in‐vitro models. All the compounds were found stable in solution form for studied period 12–68 hours and showed good lipophilic values in the range of logP 0.66–0.85. In context to biological activities, selenium compounds showed better antimicrobial (ranging 17.4±0.5–25.3±0.8 mm against S. aureus and 18.6±0.7–24.1±0.9 against E.coli at concentration of 0.3 mg/mL for both strains) and antioxidant potential (IC50 ranging 40.0–62.0 μg/mL for DPPH solutions) compared to respective ligands. The interaction study of compounds (1 s –4 s ) to DNA and BSA showed prominent binding affinity. Abstract : Synthesis of selenium based N‐heterocyclic carbene adducts is of great interest in the field of Inorganic synthesis for medicinal applications. Mono nuclear selenium adducts has been synthesized and confirmed through spectroscopic and spectrometric approach and their biological characteristics also discussed against multiple microbial strain. Moreover, their affinity with biological molecules have also been studied and discussed.